(x+y) is the coefficient of xy
I'm sorry but what are we answering? i'd love to help but i'm confused
Step-by-step explanation:
7e=the money she makes from earrings
13n=the money she makes from necklace
Answer:
it is easy use the formula of triangle which is 1/2(base × height) and base is the side where the height touches and height means the perpendicular line.
And in some cases there may be the use of pythagoras theorem
The expression can be solved by expanding the bracket and multiplying out the terms
![(p^4-q^4)(p^4+q^4)](https://tex.z-dn.net/?f=%28p%5E4-q%5E4%29%28p%5E4%2Bq%5E4%29)
![\begin{gathered} =p^4(p^4+q^4)-q^4(p^4+q^4) \\ =p^8+p^4q^4-p^4q^4-q^8 \\ =p^8-q^8 \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20%3Dp%5E4%28p%5E4%2Bq%5E4%29-q%5E4%28p%5E4%2Bq%5E4%29%20%5C%5C%20%3Dp%5E8%2Bp%5E4q%5E4-p%5E4q%5E4-q%5E8%20%5C%5C%20%3Dp%5E8-q%5E8%20%5Cend%7Bgathered%7D)
Therefore, the expression can be simplified as;
![p^8-q^8](https://tex.z-dn.net/?f=p%5E8-q%5E8)
Alternatively, using the theorem of difference of two squares, which is
![a^2-b^2=(a-b)(a+b)](https://tex.z-dn.net/?f=a%5E2-b%5E2%3D%28a-b%29%28a%2Bb%29)
Hence,
![p^8-q^8=(p^4)^2-(q^4)^2](https://tex.z-dn.net/?f=p%5E8-q%5E8%3D%28p%5E4%29%5E2-%28q%5E4%29%5E2)